Becoming an Ironman triathlete. Extreme exercise, gender equality and the family puzzle. Issue 9 (2nd September 2018) - Andreasson, Jesper; Johansson, Thomas; Danielsson, Tom
Abstract: Departing from a qualitative research approach, this article focuses on Swedish amateur Ironman triathletes and their family life. The purpose of the paper is to investigate how an elite amateur lifestyle is upheld and balanced with the demands of a sustainable family and social life. The results indicate that the process of becoming and staying an Ironman creates tensions in intimate relationships, making it hard to bring the family life puzzle together. Although the participants interviewed often talk about family life in terms of sharing things fairly equally, in terms of gender equity and involved parenthood, this seemingly is not always an easy ideal to fulfil in practice. On a broader cultural level, these findings can thus be contextualized in relation to discourses associated with the gendering of families and functions, and, of course, the gender of sport and performance.